Clinical translation and regulatory aspects of CAR/TCR-based adoptive cell therapies: the German Cancer Consortium approach - Krackhardt, Angela; Anliker, Brigitte; Hildebrandt, Martin; Bachmann, Michael; Eichmüller, Stefan B.; Nettelbeck, Dirk M.; Renner, Matthias; Uharek, Lutz; Willimsky, Gerald; Schmitt, Michael; Wels, Winfried S.; Schüssler-Lenz, Martina (Cancer immunology immunotherapy, 2018)
Adoptive transfer of T cells genetically modified by TCRs or CARs represents a highly attractive novel therapeutic strategy to treat malignant diseases. Various approaches for the development of such gene therapy medicinal products (GTMPs) have been initiated by scientists in recent years. To date, however, the number of clinical trials commenced in Germany and Europe is still low. Several hurdles may contribute to the delay in clinical translation of these therapeutic innovations including the significant complexity of manufacture and non-clinical testing of these novel medicinal products, the limited knowledge about the intricate regulatory requirements of the academic developers as well as limitations of funds for clinical testing. A suitable good manufacturing practice (GMP) environment is a key prerequisite and platform for the development, validation, and manufacture of such cell-based therapies, but may also represent a bottleneck for clinical translation. The German Cancer Consortium (DKTK) and the Paul-Ehrlich-Institut (PEI) have initiated joint efforts of researchers and regulators to facilitate and advance early phase, academia-driven clinical trials. Starting with a workshop held in 2016, stakeholders from academia and regulatory authorities in Germany have entered into continuing discussions on a diversity of scientific, manufacturing, and regulatory aspects, as well as the benefits and risks of clinical application of CAR/TCR-based cell therapies. This review summarizes the current state of discussions of this cooperative approach providing a basis for further policy-making and suitable modification of processes.